The safety and efficacy of prednisolone in preventing reaccumulation of ascites among endomyocardial fibrosis patients in Uganda: a randomized clinical trial. (December 2015) - Nabunnya, Yvonne; Kayima, James; Longenecker, Chris; Josephson, Richard; Freers, Juergen
Abstract Background Endomyocardial fibrosis (EMF), the commonest restrictive cardiomyopathy worldwide, is characterized by inflammation and fibrosis of the endocardium. Inflammation in other parts of the body such as the peritoneum has been described and may explain the accumulation of ascites, a painful and disabling feature of this disease. We determined the efficacy and safety of prednisolone to prevent re-accumulation of ascites among EMF patients attending Mulago hospital cardiology service. Methods This was a pilot randomised placebo controlled trial with a 1:1 parallel design. Over a period of 10 months, participants were recruited and randomized to receive 1 mg/kg per day of prednisolone or placebo and were followed for a maximum of 8 weeks. The primary outcome was re-accumulation of ascites from baseline (grade 2) to grade 3. Safety was assessed by self-reported side effects, physical exam, and laboratory assessment. Results Sixteen study participants were randomised to prednisolone, while nineteen were randomised to placebo. Six were lost to follow up (1-prednisolone arm, 5-placebo). Baseline characteristics were similar between groups. Prednisolone was safely administered in this setting. There was no statistically significant difference in the overall risk of developing grade 3 ascites over 8 weeks. RR (95 % confidence interval) 0.70 (0.43–1.11), P value 0.12. The rate of the primary outcome per 1000 person days of follow-up was also similar in both arms P value 0.63. Conclusion Short term prednisolone use was generally safe and did not prevent reaccumulation of ascites in this study population. Trial registration number: ISRCTN63999319, 28/03/2013